ASCORBIC ACID CONTENT OF VARIOUS MEXICAN CHILLIES - SENOSIAIN; GIRAL, FRANCISCO; E JONGUITUD, JUAN (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1940)
The author made a thorough pathological and bacteriological study of a human case of brucellosis The paper includes a rather complete review of the literature on the pathology of the disease
CIENC MEX
Keywords: ASCORBIC ACID, MEXICAN CHILLIES; MULTIDISCIPLINARIA; AGRONOMIA; PRODUCCION DE CULTIVOS